On the investment potential of Bessel-Riesz - Cerutti, R. (Nexo Revista Científica, 2010)
In this paper the inversion of a convolution type operator is obtained by using hypersingular integral technics. The Bessel- Riesz operator of a function φ belonging to S, the space of test functions of Schwartz, is definied by the convolution with the generalized functions Wα(P±i0,m,n) expressible in terms of the Bessel function of first kind Jr Wα(P±i0,m,n) is also an infinite linear combination of the ultrahyperbolic Riesz kernel of differents orders. This fact allows us to invert the Bessel-Riesz potential in an analogue manner of the ultrahyperbolic Bessel potentials (cf. [01]) and causal Riesz potentials (cf. [2]). Keywords: Riesz potential; hypersingular integral. DOI: 10.5377/nexo.v23i2.239 Nexo: Revista Científica Vol. 23, No. 02, pp.62-68/Nov 2010